Navigating Unsettling Intercultural Issues of Volunteer Tourism: A Synthetic Review - Khadka, Gopal (KMC Research Journal, 2023)
In light of the burgeoning research and operational facets of international volunteer tourism, a discernible surge in the engagement of global volunteers for cross-cultural interactions within Global South communities has become increasingly evident. However, global volunteers encounter formidable challenges during their transition into and engagement with the local host community, stemming from a conspicuous paucity of intercultural awareness. This predicament poses a substantial impediment to the aspirational objective of effectuating a beneficial and constructive impact on cross-cultural interaction with the host community. With an intercultural sensitivity lens, this synthetic review examines the major issues surrounding cross-cultural understanding and interactive learning as well as discusses potential mitigating strategies that nurture intercultural sensitivity, making transition and participation more effective for the well-being of the host community. The review suggests that cultural stereotyping, ethnocentric behaviors, self-fulfilling behaviors of volunteers, and the absence of meaningful local participation in co-production of knowledge in volunteer tourism appear to be key factors affecting meaningful cross-cultural interactions and ethical behaviors. The proposed strategies including pre-departure training and orientation as educational discipline, aimed at facilitating cross-cultural immersion, assimilation and interaction, seem to be neglected in practice of volunteering tourism. This oversight undermines the effectiveness of these crucial initiatives in achieving their intended outcomes.